Islamic Leadership School Curriculum Development in Taruna Panatagama Putri Yogyakarta - Hendro Widodo; Nurfitrianti Nurfitrianti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This research focuses on the process of curriculum development at Islamic Leadership School (ILS) in Taruna Panatagama Yogyakarta. This study aims to determine the concept and implementation of ILS curriculum development and its implications for learning outcomes. The method used in this research is descriptive qualitative method. The subjects were the founder, the Principal, the Caregiver, the teachers, the students and the alumni of the ILS Taruna Panatagama School. The data were obtained through interviews, observation, and documentation. The data were analyzed by using Spradley model, namely data analysis and data collection processes carried out simultaneously, consisting of analysis of conceptual domain information, taxonomic analysis (exploring important domains and subdomains by referring to library materials to obtain in-depth understanding), componential analysis (contrasting elements in the domains obtained and the subsequent relevant categorization), and theme analysis. The results of the study indicate that the curriculum with a homeschooling model has been built based on the potential development of each student. The basic concepts and ideas are applied based on Islamic teachings with a focus on leadership competencies by building awareness of Islamic personality and developing leadership. The implications for student learning outcomes are the changes in attitudes and behavior of students and achievements.